Pluto's interaction with the solar wind. Issue 5 (14th May 2016) - McComas, D. J.; Elliott, H. A.; Weidner, S.; Valek, P.; Zirnstein, E. J.; Bagenal, F.; Delamere, P. A.; Ebert, R. W.; Funsten, H. O.; Horanyi, M.; McNutt, R. L.; Moser, C.; et al.
Abstract: This study provides the first observations of Plutogenic ions and their unique interaction with the solar wind. We find ~20% solar wind slowing that maps to a point only ~4.5 RP upstream of Pluto and a bow shock most likely produced by comet‐like mass loading. The Pluto obstacle is a region of dense heavy ions bounded by a "Plutopause" where the solar wind is largely excluded and which extends back >100 RP into a heavy ion tail. The upstream standoff distance is at only ~2.5 RP . The heavy ion tail contains considerable structure, may still be partially threaded by the interplanetary magnetic field (IMF), and is surrounded by a light ion sheath. The heavy ions (presumably CH4 + ) have average speed, density, and temperature of ~90 km s −1, ~0.009 cm −3, and ~7 × 10 5  K, with significant variability, slightly increasing speed/temperature with distance, and are N‐S asymmetric. Density and temperature are roughly anticorrelated yielding a pressure ~2 × 10 −2  pPa, roughly in balance with the interstellar pickup ions at ~33 AU. We set an upper bound of <30 nT surface field at Pluto and argue that the obstacle is largely produced by atmospheric thermal pressure like Venus and Mars; we also show that the loss rate down the tail (~5 × 10 23  s −1 ) is only ~1% of the expected total CH4 loss rate from Pluto. Finally, we observe a burst of heavy ions upstream from the bow shock as they are becoming picked up and tentatively identify an IMF outward sector at the time of the NH flyby. Key Points: First observations of heavy ions from Pluto and their unique interaction with the solar wind Discovery of a Plutopause with an upstream standoff distance at two and a half Pluto radii Discovery of heavy ion tail behind Pluto losing 5 × 10 23 ions per second